Unveiling the Texture Secrets of Morchella Germplasm: Advanced Grading and Quality Assessment Through Texture Profile Analysis (TPA) - Jialiang Li; Ying Chen; Xuelian Cao; Jie Tang; Liyuan Xie; Lixu Liu; Yan Wan; Rongping Hu (Foods)
Morchella is an edible mushroom with medical applciations. To explore the correlation between the texture indices of Morchella and to establish a sensory quality evaluation system, the texture quality characteristics of 214 Morchella germplasm resources from our country were analyzed via the Texture Profile Analysis (TPA) method on a texture analyzer. The research revealed significant differences in the texture quality characteristics of both the pileus and stipe among Morchella populations. After the Kolmogorov–Smirnov test, the six texture characteristics were seen to conform to a normal distribution. According to the correlation analysis, there was a significant correlation between the texture characteristics of the pileus, and a significant positive correlation between the hardness and the gumminess of the stipe (correlation coefficient of 0.96). Additionally, the hardness was negatively correlated with cohesiveness and resilience, with correlation coefficients of −0.51 and −0.38. Variation analysis indicated abundant genetic variation in each characteristic. Furthermore, the coefficient of variation for the characteristics of Morchella sextalata was higher than those of other species. Principal component analysis simplified the texture evaluation indices of Morchella pileus into a palatable factor and cohesive factor, and arranged the texture evaluation indexes of Morchella stipe into toughness–hardness factor and cohesive factor. Through comprehensive evaluation and cluster analysis, 10 Morchella strains were selected for subsequent use as breeding or cultivation materials. By comparing three different methods, the ‘probability grading method’ was determined to be the most suitable evaluation method for the texture quality characteristics of Morchella. The research results established a texture evaluation system for Morchella, offering a reference for selecting and cultivating breeds with superior texture qualities.